2019
DOI: 10.1071/an17641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a buccal meloxicam formulation on the behavioural response to ring castration of calves

Abstract: This study aimed to evaluate the effect of a buccal meloxicam formulation on the behavioural response to ring castration of calves. Sixty, 3-month-old, Angus calves (40 males, 20 females) were allocated to one of three treatments (n = 20 calves/treatment): (1) rubber ring castration (RING), (2) buccal formulation of meloxicam plus rubber ring castration (RING + BUCC) and (3) handled only (CON). After treatment, calves were observed in five pens (n = 4 calves/treatment/pen) and behaviour individually recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…reported reduced plasma cortisol and haptoglobin concentrations following meloxicam administration so it would have been interesting to see if this coincided with behavioural changes as well. Conversely,Sutherland et al (2018) reported no improvement in pain behaviours following meloxicam administration. However, meloxicam was under-dosed; the datasheet states a dose of 0.5 mg/kg and each calf was administered 5 ml (at 10 mg/ml), but as mean calf weight was 111.7 kg the mean dose should have been 5.6 ml.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…reported reduced plasma cortisol and haptoglobin concentrations following meloxicam administration so it would have been interesting to see if this coincided with behavioural changes as well. Conversely,Sutherland et al (2018) reported no improvement in pain behaviours following meloxicam administration. However, meloxicam was under-dosed; the datasheet states a dose of 0.5 mg/kg and each calf was administered 5 ml (at 10 mg/ml), but as mean calf weight was 111.7 kg the mean dose should have been 5.6 ml.…”
mentioning
confidence: 91%
“…Ketoprofen was generally administered at a total dose of 3 mg/kg and flunixin was administered at variable doses of 3.33 mg/kg (Kleinhenz et al, 2018), 200 mg (Paull et al, 2015) and 1.1 mg/kg(Webster et al, 2013). It is also worth noting that in on-farm situations calf weight may be estimated, resulting in incorrect dose calculations and therefore ineffective analgesia, as inSutherland et al (2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…may contribute to this non-descript administration outcome. For example, while some chose to assess Activity using accelerometers [ 27 ], others relied on behavioral observations of pen (e.g., walking) [ 31 ] or chute [ 28 ] activities. Such inconsistencies further limit the development of robust conclusions and recommendations for pain management in cattle.…”
Section: Resultsmentioning
confidence: 99%